THE SIGNIFICANCE OF FINANCIAL LITERACY FOR MUSLIM WOMEN IN MANAGING FAMILY FINANCE - Wan Noor Hazlina Wan Jusoh; Nor Faezah Ghazi Ahmad; Muhammad Hamdan Syafieq Ahmad (Journal of Islamic, Social, Economics and Development, 2022)
modern woman wears multiple hats - from a loving daughter and nurturing wife to a selfless mother and dedicated employee. On top of meeting her household responsibilities and family commitments, she also makes a mark outside and pursues a successful professional life. And yet, most women seem to be neglecting a very crucial aspect of their life: personal finances. Generally, women play an important role in managing family finance since financial planning is essential for financial wellbeing of a family. While on the one hand, the role of financial planning is largely acknowledged, on the other hand the significance of financial literacy is still lagging, especially for women. Women consistently score lower than men on financial literacy measures, and this gender-based gap may negatively impact not only the financial well-being of women themselves but also their families. Thus, this study aims at explaining the significance of financial literacy for Muslim women in managing family finance. Library research is used to discuss the significance of financial literacy for Muslim women in managing family finance and how Islam looks at it. It is found that Muslim women play a significant role in managing family finance to ensure family wealth management, family wellbeing, and Shari’ah-compliant financial practices.